2018
DOI: 10.1177/0042098018776921
|View full text |Cite
|
Sign up to set email alerts
|

Electricity services always in the making: Informality and the work of infrastructure maintenance and repair in an African city

Abstract: Access to 'formal' electricity networks remains a key challenge in many African urban areas. Significant attention has been paid to how access to an electricity connection should be provided, with much less attention paid to how electricity infrastructures are operated and maintained. Attention to how utilities govern the challenges inherent to 'informality' in the production of 'formal' networked infrastructure is less common, especially in African cities. Moreover, with a few notable exceptions, studies on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 53 publications
1
59
0
3
Order By: Relevance
“…The role of patchwork in the adaptation of the formal network, and in the provision of urban modernity, echoes findings from other cities and spaces across the Global South. The constant work that infrastructures require resonates with notions of service provision being always in the making (Baptista, 2019). Unfinished and ongoing, infrastructure and the relations it enables are constantly being adapted in relation to changing socio-material conditions.…”
Section: Patchworking Urban Modernitymentioning
confidence: 99%
“…The role of patchwork in the adaptation of the formal network, and in the provision of urban modernity, echoes findings from other cities and spaces across the Global South. The constant work that infrastructures require resonates with notions of service provision being always in the making (Baptista, 2019). Unfinished and ongoing, infrastructure and the relations it enables are constantly being adapted in relation to changing socio-material conditions.…”
Section: Patchworking Urban Modernitymentioning
confidence: 99%
“…Despite popular believe, the problem of deteriorating water and sanitation services is not solely attributable to lack funding. An extensive World Bank study in 2011 identified no relation between levels of public spending and the levels of access to water supply and sanitation in different countries of Africa (see Baptista, 2019 ). The problem could be in the funding models which have been used over the years.…”
Section: Factors Influencing Sustainable Interventionsmentioning
confidence: 99%
“…Suzanne Mills’ (2019; Mills and Clarke, 2009) work has been the exception, highlighting the gendered and colonial politics of labour in Canadian infrastructure projects. In other research, workers become visible in different ways in accounts of urban informality and socio-technical infrastructures (Baptista, 2019; Hall et al, 2017; Kelly-Richards and Banister, 2017; Thieme, 2018), food deserts (Deener, 2017) and urban environmental politics (Doshi, 2019), but are often not central to the conceptualization of infrastructure. The displacements and inequities of infrastructure make it a useful conceptual starting point for exploring forms of precarity, however.…”
Section: Labour and Infrastructurementioning
confidence: 99%